Association between C reactive protein and microvascular and macrovascular dysfunction in sub-Saharan Africans with and without diabetes: the RODAM study. Issue 1 (14th July 2020) - Hayfron-Benjamin, Charles Frederick; Maitland-van der Zee, Anke H; van den Born, Bert-Jan; Amoah, Albert G B; Meeks, Karlijn A C; Klipstein-Grobusch, Kerstin; Schulze, Matthias B; Spranger, Joachim; Danquah, Ina; Smeeth, Liam; Beune, Erik J A J; Mockenhaupt, Frank; et al.
Abstract : Introduction: Although inflammation assessed by elevated C reactive protein (CRP) concentration is known to be associated with risk of cardiovascular disease, its association with microvascular and macrovascular dysfunction in diabetes and non-diabetes remains unclear. We examined the association between CRP and diabetes and associated microvascular and macrovascular dysfunction in sub-Saharan Africans with and without diabetes. Research design and methods: Cross-sectional analyses of baseline data from the multicenter RODAM study (Research on Obesity and Diabetes among African Migrants) including 5248 Ghanaians (583 with diabetes, 4665 without diabetes) aged 25–70 years were done. Logistic regression analyses were used to examine the associations between CRP Z-scores and diabetes and microvascular (nephropathy) and macrovascular (peripheral artery disease (PAD)) dysfunction, with adjustments for age, sex, site of residence, smoking, body mass index, systolic blood pressure, and low-density lipoprotein cholesterol. Results: In the fully adjusted models, higher CRP concentration was significantly associated with diabetes (adjusted OR 1.13; 95% CI 1.05 to 1.21, p=0.002). In participants with diabetes, higher CRP concentration was associated with PAD (1.19; 1.03 to 1.41, p=0.046) but not nephropathy (1.13; 0.97 to 1.31, p=0.120). Among participants without diabetes, higher CRP concentration was associated with higher odds of PAD (1.10; 1.01 to 1.21, p=0.029) and nephropathy (1.12; 1.04 to 1.22, p=0.004). Conclusions: In this study, higher CRP concentration was associated with higher odds of diabetes in sub-Saharan Africans. Also, higher CRP concentration was associated with higher odds of nephropathy and PAD in non-diabetes and higher odds of PAD in diabetes. CRP may be an important marker for assessment of risk of diabetes and risk for PAD and nephropathy in sub-Saharan Africans with and without diabetes.